2022
DOI: 10.3390/nano12213845
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Contact Engineering of Field-Effect Transistor Based on Two-Dimensional Materials

Abstract: Two-dimensional (2D) semiconductors have been considered as promising candidates to fabricate ultimately scaled field-effect transistors (FETs), due to the atomically thin thickness and high carrier mobility. However, the performance of FETs based on 2D semiconductors has been limited by extrinsic factors, including high contact resistance, strong interfacial scattering, and unintentional doping. Among these challenges, contact resistance is a dominant issue, and important progress has been made in recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…This fact may indicate the presence of the Fermi level pinning effect at the contact of the metal and the two-dimensional organic region. A similar phenomenon was previously observed, not only on conventional metal/polymer interfaces [ 6 ] but also on interfaces such as 3D metal/2D material [ 59 ]. In [ 60 ], it was experimentally shown that the pinning of the Fermi level at the metal–2D semiconductor interface can be caused by defects formed during the manufacture of electrodes.…”
Section: Resultssupporting
confidence: 83%
“…This fact may indicate the presence of the Fermi level pinning effect at the contact of the metal and the two-dimensional organic region. A similar phenomenon was previously observed, not only on conventional metal/polymer interfaces [ 6 ] but also on interfaces such as 3D metal/2D material [ 59 ]. In [ 60 ], it was experimentally shown that the pinning of the Fermi level at the metal–2D semiconductor interface can be caused by defects formed during the manufacture of electrodes.…”
Section: Resultssupporting
confidence: 83%
“…Until now, most research efforts on Fermi-level pinning have focused on optimizing electrode contacts in solar cells [27][28][29] and gate characteristics in field-effect transis-tors [30][31][32][33][34]. Research on Fermi-level pinning in the hot carrier detection devices has mainly focused on enhancing the photoelectric response in the visible to near-infrared wavelength range [14][15][16].…”
Section: Introductionmentioning
confidence: 99%